Test−Retest Reliability of Isokinetic Ankle, Knee and Hip Strength in Physically Active Adults Using Biodex System 4 Pro - Tuominen, Juho; Leppänen, Mari; Jarske, Heidi; Pasanen, Kati; Vasankari, Tommi; Parkkari, Jari (Methods and protocols, 2023)
Background: The isokinetic dynamometry is considered a gold standard in muscle strength testing. The reliability of lower limb isokinetic strength measurements has not been thoroughly evaluated. Objective: To examine the test−retest reliability of isokinetic ankle plantar and dorsiflexion, ankle inversion and eversion, knee extension and flexion and hip abduction and adduction strength in physically active adults using Biodex System 4 Pro. Methods: Peak torques (PTs) and average peak torques (APTs) of the dominant and nondominant lower limbs were tested twice in 19 physically active adults 7 to 14 days apart. Results: The intraclass correlation coefficients (ICC) values varied from excellent to moderate and coefficient of variation of typical error (CVTE) values were 6.6–19.5%. Change in the mean expressed as a percent varied from −3.1% to 9.6%. There was no difference in the reliability between PT and APT values. Dominant lower limb was more reliable in every case if there was difference between limbs. Conclusion: Test−retest reliability of isokinetic ankle, knee and hip strength in physically active adults using Biodex System 4 is mostly good or excellent. However, the observed range of the random variation has to be noted when using it in scientific follow-up studies or evaluation of patient progress in clinical settings.